Cultura organizacional e liderança: estudo de caso em uma instituição pública do setor bancário no Brasil - Sarmento, Eva Seloi Santos (Universidade do Vale do Rio dos Sinos, 2015)
This study aimed to investigate how the interrelationships between organizational culture and leadership in a Brazilian public company of the banking sector through a survey. This dissertation uses the Model Denison (2012) to investigate on Organizational Culture and the model of Bass and Riggio (2006) to find transformational leadership. A quantitative approach study was conducted out and used a questionnaire validated in the Portuguese reality Lousã (2013), and the analysis of the data was processed by SPSS V tool 20. Obtained 964 respondents and the results, show that culture and leadership are correlated each other in the company searched. It was observed also that there are no perceived differences between the regions of the country, although there are differences between leaders and subordinates, indicating the existence of subcultures. In addition, the results show that some items considered strategic to the organization are not perceived as such by both leaders and led. Aspects related to the goals and objectives in relation to the organizational culture and inspirational motivation with regard to transformational leadership, require further attention by the company studied. As future studies, it is recommended innovation survey to compare with the results of research carried out in Portugal as well as a qualitative study to examine whether the perception of leaders refer to themselves or their immediate leaders. Also, it is recommended conducting research in other areas of the company that were not addressed in this study and research on the cohabitation between generations, justified by the amplitude of age that the company hires.
Keywords: Cultura organizacional; Liderança; Organização bancária brasileira; Organizational culture; Leadership; Brazilian banking organization; ACCNPQ::Ciências Sociais Aplicadas::Administração